Active Versus Passive Transcutaneous Bone Conduction Hearing Devices: A Systematic Review and Meta-Analysis. Issue 1 (29th January 2022) - Forner, David; Noel, Christopher W.; Horwich, Peter; Hong, Paul; Shoman, Nael
Abstract : Supplemental Digital Content is available in the text. Abstract : Objectives: Active and passive transcutaneous devices (tBCHDs) have been introduced in an effort to address complication concerns with percutaneous devices. Direct comparison of active and passive devices through evidence synthesis practices is incomplete. This systematic review and meta-analysis sought to synthesize and compare available evidence on audiological, quality of life, and complication-related outcomes of active and passive tBCHDs. Design: MEDLINE, EMBASE, CINAHL, and Cochrane CENTRAL were searched from inception to September 23, 2019. Observational and experimental studies investigating active or passive tBCHDs in adults were eligible. Studies were screened independently in duplicate. This study is reported in accordance with the PRISMA guidelines. Risk of bias and quality assessments were completed using the Newcastle-Ottawa Scale and the Quality Appraisal Tool for Case Series. Meta-analysis was performed with random-effects models. Audiological outcomes included changes in pure-tone average, functional hearing, and high-frequency hearing. Quality of life outcomes included patient-reported results. Complications included minor, major, and total complications experienced. Results: One thousand five hundred forty-two nonduplicate articles were screened. Twenty-eight studies were included. Quality of included studies was low overall. The pooled complication rate for active devices was 14.8% (95% confidence interval: 0.09–0.21, I 2 : 0%). The pooled improvement in functional hearing for active devices among those with mixed or conductive hearing loss was 31.8 dB (95% confidence interval: 27.7–35.9, I 2 : 44.6). Improvement in functional hearing ranged from 25.2 to 44.3 dB for passive devices. Active devices provided improved high-frequency hearing compared to passive devices: the weighted average hearing gains at 2, 3, 4, and 6 kHz were 26.5, 25.7, 31.8, and 34.3 dB for active devices and 26.2, 21.1, 16.8, and 6.4 dB for passive devices, respectively. Both device types demonstrated improvement in ease of communication, reverberation, and understandability in background noise. Conclusions: Both active and passive tBCHDs demonstrate acceptable safety profiles and QoL improvements. Active devices may provide better hearing outcomes, especially in high frequencies, but high-quality comparative studies are lacking. Future work is needed in this regard.